Riesgo cardiovascular en pacientes con FINDRISC-C mayor o igual a 12 - Cuello Santana, Karen Lucía; Mariano Cantillo, Harold José; Ocampo Romero, Diego Fernando; Candelario Restrepo, Heider Keyvis; Tovar Fernández, Edison Armando; Yancy Caballero, Henry Giovanny (Repertorio de medicina y cirugía, 2023)
Introduction: the FINDRISC tool allows calculating the risk for developing diabetes, with a cutoff point of 12 for Colombia.  There is evidence that cardiovascular risk (CVR) increases as this score increases, but there is no information when the value is ≥ 12 in Colombia. Objective: to establish CVR in patients with a FINDRISC-C of 12 or higher based on the adjusted Framingham risk score for Colombia.  Materials and Methods: retrospective cross-sectional sub-analysis in which the FINDRISC-C questionnaire was administered to 796 patients, of which 293 had a score of 12 or higher and 262 met the eligibility criteria. CVR was calculated by univariate and multivariate analyses, statistic significances and multiple correspondence analysis. Results: of 262 patients, 63% women, 87% had overweight and obesity, average abdominal circumference was 97 cm, 10% smoked and 48% had a family history of type 2 diabetes mellitus. A CVR media of 8.10 (CI 7.29-8.91) was found, the mean score for each category when stratifying the FINDRISC-C was: moderate FINDRISC-C (7.83); high FINDRISC-C (7.87), very high FINDRISC-C (12.61).  The prevalence of dyslipidemia was 46.2 % (CI 95%: 40-50), higher among men (53.6%). Conclusion: patients with a FINDRISC-C ≥ 12 have a moderate to high CVR.  As the FINDRISC-C value increases, risk percentage, estimated on the basis of the adjusted Framingham risk score for Colombia, tends to increase.  The prevalence of dyslipidemia among patients with FINDRISC-C ≥ 12 was elevated. Introducción: la herramienta FINDRISC permite calcular el riesgo de desarrollar diabetes con punto de corte para Colombia de 12.  Existe evidencia de que el riesgo cardiovascular se incrementa a medida que lo hace el puntaje, pero en Colombia no existe información cuando es ≥ 12. Objetivo: establecer el riesgo cardiovascular (RCV) en pacientes con FINDRISK-C ≥ 12 mediante score Framingham ajustado para Colombia.  Materiales y métodos: subanálisis transversal retrospectivo en 796 pacientes a quienes se les aplicó el cuestionario FINDRISC-C, de ellos 293 con puntaje ≥ 12 y 262 cumplieron los criterios de elegibilidad. Antes se les calculó el RCV mediante análisis uni y multivariado, significancias estadísticas y análisis de correspondencias múltiple. Resultados: 262 pacientes, 63% mujeres, 87% tuvieron sobrepeso y obesidad, promedio de perímetro abdominal 97 cm, 10% eran fumadores y 48% tenían antecedente familiar de diabetes mellitus tipo 2. Se encontró una media de RCV de 8,10 (IC 7,29-8,91), al estratificar por FINDRISC-C la media para cada una de las categorías fue: FINDRISC-C moderado 7,83; FINDRISC-C alto 7,87, FINDRISC-C muy alto 12,61.  La prevalencia de dislipidemia fue de 46,2 % (IC 95%: 40-50) siendo mayor en hombres (53,6%). Conclusión: los pacientes con FINDRISC-C ≥ 12 tienen un RCV entre moderado y alto, existiendo tendencia al incremento del porcentaje de riesgo calculado según score Framingham ajustado para Colombia, a medida que aumenta el puntaje FINDRISC-C.  La prevalencia de dislipidemia en pacientes con FINDRISC-C ≥ 12 fue elevada.